Robust design of a 5MW permanent magnet synchronous generator using Taguchi method - Wen-Chang Tsai (2012 8th International Conference on Computing and Convergence Technology, 2012)
The paper presents an approach to the optimal design of a 5MW direct-drive permanent magnet synchronous generator based on the Taguchi method. Taguchi orthogonal array is employed to determine the optimal combination of design parameters, including: steel lamination material, applied voltage, slot number, diameter of air-gap, magnet pole materials, magnet pole depth, stator outer/inner diameter, and length of stator core under the rated rotational speeds. The concept of signal-to-noise (SN) ratio is applied to evaluate the performance of the permanent magnet synchronous generator. Effect of these control parameters on the output power and efficiency of the generator is analyzed in the paper. Results show that the designed 5MW direct-drive permanent magnet synchronous generator is capable of operating stably and assure the adequate 5MWpower output and good efficiency greater than 95%.